2022
DOI: 10.1002/ajpa.24501
|View full text |Cite
|
Sign up to set email alerts
|

Feeding postural behaviors and food geometric and material properties in bearded capuchin monkeys (Sapajus libidinosus)

Abstract: Objectives: Foods that are geometrically and mechanically challenging to eat have been associated with specializations in feeding behavior and craniodental morphology across primates, and many of these foods are embedded, requiring a variety of positional behaviors during feeding. However, variation in positional behaviors in response to food properties is not well understood. Here, we examine differences in feeding postural behaviors across feeding events in relation to substrate and food geometric and materi… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

2
12
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
6

Relationship

3
3

Authors

Journals

citations
Cited by 7 publications
(14 citation statements)
references
References 109 publications
(202 reference statements)
2
12
0
Order By: Relevance
“…In addition, foods requiring high forces to initiate fracture, regardless of embedded status, may constrain behavioral flexibility, such that a few, specific behaviors are routinely employed to process these foods. This is consistent with Laird et al (2020, 2022) who found certain ingestive and postural behaviors are more common with mechanically challenging foods. Robust capuchins may have a limited suite of manual and ingestive behaviors in their repertoire that they can employ to effectively fracture foods with high FMPs.…”
Section: Discussionsupporting
confidence: 92%
See 3 more Smart Citations
“…In addition, foods requiring high forces to initiate fracture, regardless of embedded status, may constrain behavioral flexibility, such that a few, specific behaviors are routinely employed to process these foods. This is consistent with Laird et al (2020, 2022) who found certain ingestive and postural behaviors are more common with mechanically challenging foods. Robust capuchins may have a limited suite of manual and ingestive behaviors in their repertoire that they can employ to effectively fracture foods with high FMPs.…”
Section: Discussionsupporting
confidence: 92%
“…In addition, foods requiring high forces to initiate fracture, regardless of embedded status, may constrain behavioral flexibility, such that a few, specific behaviors are routinely employed to process these foods. This is consistent with Laird et al (2020Laird et al ( , 2022 fracture foods with high FMPs. In this way, FMPs and embedded status may play a significant role in shaping inter and intraspecific food processing behaviors (Visalberghi et al, 2016;Wright et al, 2009).…”
Section: Discussionsupporting
confidence: 85%
See 2 more Smart Citations
“…Processing this fruit induces repeated loads on L. catta’s thin-enameled teeth, as they repeatedly bite the pod to induce cracking; this is likely a significant contributor to high rates of dental wear and tooth loss in this L. catta population [ 32 ]. Observations of the ingestive behaviors and mechanical properties of foods eaten by Sapajust libidinosus in Brazil [ 33 , 34 , 35 ] coupled with captive research on mandibular strain and muscle fiber architecture in this species [ 36 , 37 ] suggest that ingestive behaviors, particularly those related to high mandibular strain, are important pressures on craniodental morphology in robust capuchin monkeys. Dental and cranial traits of Gorilla gorilla gorilla , including thick enamel and increased molar-shearing crests, are generally assumed to facilitate the processing of tough, fracture-resistant foods such as leaves and fibrous vegetation [ 38 ].…”
Section: Introductionmentioning
confidence: 99%